2014
DOI: 10.1007/s00221-014-4118-3
|View full text |Cite
|
Sign up to set email alerts
|

Visual detail about the body modulates tactile localisation biases

Abstract: 1The localisation of tactile stimuli requires the integration of visual and somatosensory inputs within 2 an internal representation of the body surface, and is prone to consistent bias. Joints may play a role 3 in segmenting such internal body representations, and may therefore influence tactile localisation 4 biases, although the nature of this influence remains unclear. Here, we investigate the relationship 5 between conceptual knowledge of joint locations and tactile localisation biases on the hand. In one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(89 citation statements)
references
References 27 publications
30
59
0
Order By: Relevance
“…Consistent with our previous results (Mancini et al, 2011;Margolis & Longo, 2015), there were clear constant errors in tactile localisation in the Skin Localisation Task1 (see Figures 9-10). There was a highly significant distal bias (.434 Bookstein units), t(11) = 9.90, p < .0001, as well as a radial bias (i.e., towards the thumb; .132 Bookstein units), t(11) = 5.61, p < .0005.…”
Section: Constant Errorssupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with our previous results (Mancini et al, 2011;Margolis & Longo, 2015), there were clear constant errors in tactile localisation in the Skin Localisation Task1 (see Figures 9-10). There was a highly significant distal bias (.434 Bookstein units), t(11) = 9.90, p < .0001, as well as a radial bias (i.e., towards the thumb; .132 Bookstein units), t(11) = 5.61, p < .0005.…”
Section: Constant Errorssupporting
confidence: 81%
“…In previous studies (Mancini et al, 2011;Margolis & Longo, 2015), we found stereotyped biases (i.e., constant errors) in the localisation of tactile stimuli on the hand dorsum. If these biases also influence tactile spatial remapping, they should appear in the present experiment when participants judge the spatial location of touch (which requires tactile localisation on the skin), but not when participants localise verbally-given landmarks (which does not require tactile localisation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the same effect was found when participants judged the locations of the experimenter's knuckles, suggesting that it does not reflect something about people's representations of their own hands specifically, but rather something about their conceptual understanding of hands in general. Margolis and Longo (2015) found a similar distal bias when participants were asked to locate their knuckles on a silhouette image of their hand.…”
Section: Distortions In Higher-level Body Representationsmentioning
confidence: 90%
“…We have recently reported large misunderstandings about the location of other joints in the hand – the knuckles – which people appear to believe are substantially farther forward in the hand than they actually are (Longo, 2015b; Margolis and Longo, 2015). Indeed, we found that the magnitude of this bias was correlated across participants with the extent of underestimation of finger length in the hand mapping task (Longo et al, 2015c).…”
Section: Discussionmentioning
confidence: 99%